Childhood adversities are common among trans people and associated with adult depression and suicidality. (September 2021) - Biedermann, Sarah V.; Asmuth, Janina; Schröder, Johanna; Briken, Peer; Auer, Matthias K.; Fuss, Johannes
Abstract: Trans people suffer from increased rates of depression and suicidality even after gender-affirming medical interventions. The present study aims to examine the prevalence of childhood adversities in patients with gender dysphoria and to analyze its impact on adult depression and suicidality. Participants meeting diagnostic criteria of Gender Dysphoria were recruited in a cross-sectional multicenter study at four German health-care centers. Childhood adversities were assessed with the Childhood Trauma Questionnaire (CTQ) and additional single items for other childhood adversities. Associations between childhood adversities and adult depression and suicidality were calculated using regression analyses. A large majority of participants reported childhood adversities, and only 7% endorsed no adversities in the CTQ. Over 30% reported severe to extreme childhood adversities. One-fourth reported parents exhibiting violent behavior while bullying by peers was experienced by 70%. These adversities were associated with an increased risk for adult depression and suicidality. Time since beginning of hormonal therapy did not show a significant influence neither on depression nor on suicidality. Childhood adversities are common and associated with adult depression and suicidality in trans people. Adequately addressing these childhood adversities and providing trauma-informed mental health care might ameliorate the mental health burden in trans people. Highlights: A large majority of trans people reported childhood adversities. About one third reported severe to extreme childhood adversities. Childhood adversities contributed significantly to adult depression and suicidality. Childhood adversities should be considered in the health care of trans people.